2011
DOI: 10.1111/j.1462-2920.2010.02415.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐, rRNA‐ and mRNA‐based stable isotope probing of aerobic methanotrophs in lake sediment

Abstract: A stable isotope probing (SIP) approach was used to study aerobic methane-oxidizing bacteria (methanotrophs) in lake sediment. Oligotrophic Lake Stechlin was chosen because it has a permanently oxic sediment surface. 16S rRNA and the pmoA gene, which encodes a subunit of the methane monooxygenase enzyme, were analysed following the incubation of sediment with (13) CH(4) and the separation of (13) C-labelled DNA and RNA from unlabelled nucleic acids. The incubation with (13) CH(4) was performed over a 4-day tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
100
1
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(117 citation statements)
references
References 78 publications
10
100
1
6
Order By: Relevance
“…The majority of methylotrophs in the initial sample were affiliated with Methylophaga or Methylophilaceae, which are likely secondary consumers of C1 compounds after Methylococcaceae oxidize methane to methanol. These processes appear to be tightly coupled, but presumably require Methylococcaceae to respond initially (6,39). Methylococcaceae accounted for only 3% of sequences in the initial sample, and they appear to bloom more slowly in response to natural gas inputs than ethane and propane oxidizers, just as observed earlier in the summer (2).…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…The majority of methylotrophs in the initial sample were affiliated with Methylophaga or Methylophilaceae, which are likely secondary consumers of C1 compounds after Methylococcaceae oxidize methane to methanol. These processes appear to be tightly coupled, but presumably require Methylococcaceae to respond initially (6,39). Methylococcaceae accounted for only 3% of sequences in the initial sample, and they appear to bloom more slowly in response to natural gas inputs than ethane and propane oxidizers, just as observed earlier in the summer (2).…”
mentioning
confidence: 83%
“…Given that the cultivated strains of Colwellia are capable of degrading many different carbon sources (33,40), either explanation is possible. It is also important to note that we cannot exclude the possibility of cross-feeding (25,39), whereby one organism is responsible for the initial oxidation step (e.g., ethane to ethanol) and a different organism then consumes this 13 C-labeled intermediate (e.g., ethanol) and incorporates it into 13 C biomass. However, given the dominance of Colwellia in the SIP samples and the high rates of ethane and propane oxidation in June, when Colwellia sequences accounted for approximately 70% of sequences in plume samples (2), it is likely that Colwellia was responsible for the bulk of ethane and propane oxidation in situ, although the SIP results show the DWH Oceanospirillales may also have played a role.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While only 3 mm thick, the soil layer in the microcosm was considerably thinner and allowed a stronger focus on the organisms of interest than in many other experiments (Dumont et al, 2011, Siljanen et al, 2011. Even working at a resolution of 1 cm dilutes the active layer with the microbial seed bank in the bulk soil and limits interpretability, regardless if major soil compartments are sampled separately (Eller et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The individual species carrying out the observed activity that are collectively targeted by the qPCR assays constitute an even lower percentage of the community. Type Ia MOB related to the ones found in our study have been demonstrated to be responsible for methane consumption in many important methane-emitting habitats such as rice paddies (Bodelier et al, 2000), arctic wetlands (Graef et al, 2011), landfills (Chen et al, 2007), lake sediments (Dumont et al, 2011) and floodplains , which has been ascribed to their specific traits enabling them to be very responsive to the periodic availability of methane and other nutrients (Steenbergh et al, 2010;Bodelier et al, 2012). Recent studies assigning species-specific contributions to important biogeochemical cycles using stable isotopes also indicated a disproportionate role of single rare microbial species to globally important processes (Musat et al, 2008;Pester et al, 2010;Peter et al, 2011), strongly suggesting that the traits of the organisms involved will be fundamental to the variability and dynamics in the biogeos p e c ie s n ic h e s function Figure 7 Graphical representation of the three dimensions involved in BEF relationships.…”
Section: Synthesismentioning
confidence: 99%